The Relaxant Activity of Safranal in Isolated Rat Aortas is Mediated Predominantly via an Endothelium-Independent Mechanism -Vasodilatory mechanism of safranal- - Bibi Marjan Razavi; Mojtaba Alipoor Amanloo; Mohsen Imenshahidi; Hossein Hosseinzadeh (Korean Pharmacopuncture Institute, 2016)
Objectives: Safranal is a pharmacologically active component of saffron and is responsible for the unique aroma of saffron. The hypotensive effect of safranal has been shown in previous studies. This study evaluates the mechanism for the vasodilatory effects induced by safranal on isolated rat aortas. Methods: To study the vasodilatory effects of safranal (0.2, 0.4 and 0.8 mM), we contracted isolated rat thoracic aorta rings by using 10-6-M phenylephrine (PE) or 80-mM KCl. Dimethyl sulfoxide (DMSO) was used as a control. The vasodilatory effect of safranal was also evaluated both on intact and denuded endothelium aortic rings. Furthermore, to study the role of nitric oxide and prostacyclin in the relaxation induced by safranal, we incubated the aortic rings by using L-NAME (10-6 M) or indomethacin (10-5 M), each for 20 minutes. Results: Safranal induced relaxation in endothelium-intact aortic rings precontracted by using PE or KCl in a concentration-dependent manner, with a maximum relaxation of more than 100%. The relaxant activity of safranal was not eliminated by incubating the aortic rings with L-NAME (EC50 = 0.29 vs. EC50 = 0.43) or with indomethacin (EC50 = 0.29 vs. EC50 = 0.35), where EC50 is the half maximal effective concentration. Also, the vasodilatory activity of safranal was not modified by endothelial removal. Conclusion: This study indicated that relaxant activity of safranal is mediated predominantly through an endothelium- independent mechanism.